Method for improving bonding strength between milled surface of carbon fiber composite material and metal

By pretreating the precoating liquid of nanoparticles and epoxy resin on the milling surface of carbon fiber composites, the problem of reducing the bonding strength between carbon fiber composites and metals is solved, and a significant improvement in bonding strength and reliability are achieved.

CN119842326APending Publication Date: 2025-04-18NORTH CHINA UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411835811.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

After the carbon fiber composite material is milled, its bonding strength and reliability with metal are reduced, especially fiber peeling phenomenon, which leads to bond failure.

Method used

The bonding area of ​​the milling surface of the carbon fiber composite material is pretreated by using a precoating liquid containing nanoparticles and epoxy resin. After being wet and left to stand, the residual amount of epoxy resin is reduced, thereby improving the fiber peel strength and bonding strength.

Benefits of technology

The bonding strength between the milling surface of carbon fiber composite material and metal has been significantly improved, the average bonding strength has been increased by 75.25%, and the bonding reliability has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842326A_ABST
    Figure CN119842326A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of carbon fiber material surface treatment, and discloses a method for improving the bonding strength of a milled surface of a carbon fiber composite material and metal. According to the method, the milling face of the carbon fiber composite material is provided with a bonding area, and the bonding area is used for being bonded with metal; the bonding strength of the milled surface of the carbon fiber composite material and metal is improved by pretreating the bonding area; the pretreatment comprises the following steps: treating the bonding area by adopting a pre-coating solution; the pre-coating liquid comprises nano-particles, first epoxy resin and a solvent. The method provided by the invention overcomes the negative influence on the bonding strength after the carbon fiber composite material is machined, can effectively improve the bonding strength between the milling surface of the carbon fiber composite material and the metal, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon fiber material surface treatment, and in particular to a method for improving the bonding strength between a milled surface of a carbon fiber composite material and a metal. Background Art

[0002] Carbon fiber composites (CFRP) have good chemical stability and high strength ratio, and have unique advantages in solving the lightweight problems of energy saving, emission reduction and improving fuel efficiency. Adhesive connection has many advantages such as light connection mass, uniform stress distribution, high surface quality of the bonding area and good sealing. Therefore, the adhesive connection of carbon fiber composites and metals has been widely used in the fields of navigation, automobiles, aerospace, etc.

[0003] In actual engineering applications, although CFRP parts are usually produced with a near-net shape strategy, in order to achieve sufficient assembly accuracy and the required dimensional tolerances and other functional characteristics, the final shape of the bonded parts still needs to be processed by machining such as drilling and milling. However, the surface of the carbon fiber composite material after milling is prone to fiber peeling when bearing loads, which in turn reduces its bonding strength and reliability with the metal.

[0004] There are many methods to improve the bonding strength between carbon fiber composites and metals, but most of them are through metal surface treatment, such as vapor deposition, anodizing, etc. However, when the interfacial bonding strength of the metal is improved, its bonding failure will appear fiber tearing and peeling phenomenon, especially for machined carbon fiber composites, its bonding strength with metal will depend on the fiber peeling strength of the composite surface.

[0005] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0006] The object of the present invention is to provide a method for improving the bonding strength between the milling surface of the carbon fiber composite material and the metal, so as to solve the problem of poor bonding effect between the milling surface of the carbon fiber composite material and the metal.

[0007] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a method for improving the bonding strength between the milling surface of a carbon fiber composite material and a metal, wherein the milling surface of the carbon fiber composite material has a bonding area, and the bonding area is used to bond with the metal; the bonding strength between the milling surface of the carbon fiber composite material and the metal is improved by pretreating the bonding area; the pretreatment includes the following steps: treating the bonding area with a precoating liquid; the components of the precoating liquid include nanoparticles, a first epoxy resin and a solvent. Among them, the solvent can be selected according to the needs, which does not react with the first epoxy resin, does not affect the chemical properties of the first epoxy resin, can dilute the first epoxy resin, and can evaporate quickly.

[0008] Preferably, the pretreatment can be achieved by soaking the bonding area in a pre-coating liquid, taking it out of the pre-coating liquid and letting it stand, and then reducing the residual amount of the first epoxy resin in the bonding area. The step of standing is to allow the solvent to fully evaporate and reduce or avoid solvent residue.

[0009] Preferably, the bonding area is immersed in the pre-coating liquid for 10-15 seconds (for example, 10 seconds, 11 seconds, 12 seconds, 13 seconds, 14 seconds or 15 seconds); the standing time after taking out is 1 minute, and after standing, the residual amount of the first epoxy resin in the bonding area is reduced to 0.0017-0.0020g / 300mm 2 (For example, 0.0017g / 300mm 2 , 0.00 / 18g / 300mm 2 、0.00 / 19g / 300mm 2 or 0.0020g / 300mm 2 ) Among them, the standing time is one minute, which helps to ensure that the excess epoxy resin is wiped off after most of the solvent has evaporated, so that the viscosity of the epoxy resin in the pre-coating layer increases, and most of the epoxy resin will not be wiped off at one time, resulting in too little pre-coating layer; if the standing time is too long, the viscosity of the pre-coating layer will increase and it will be difficult to wipe; in short, standing for 1 minute can better control the residual amount of epoxy resin and nanoparticles in the pre-coating layer. If the residual amount of the first epoxy resin in the bonding area is too low, the lifting effect is not obvious; if the residual amount of the first epoxy resin in the bonding area is too large, it will cause negative effects.

[0010] More preferably, the bonding area is wiped with non-linting memory foam to reduce the amount of the first epoxy resin residue in the bonding area. During wiping, the first epoxy resin is mainly removed, and since there are many nanoparticles entering the sub-surface of the carbon fiber composite material, the nanoparticles in the bonding area are little affected during the wiping process.

[0011] Preferably, in the pre-coating solution, the mass ratio of the nanoparticles, the first epoxy resin and the solvent is 1:(38-42):360 (for example, 1:38:360, 1:39:360, 1:40:360, 1:41:360 or 1:42:360). The bonding strength first increases and then decreases with the increase in the proportion of the nanoparticles.

[0012] Preferably, before the pretreatment, the step of grinding the bonding area and the metal surface is also included. The grinding step helps to improve the bonding strength between the milled surface of the carbon fiber composite material and the metal; if this step is omitted, the bonding strength of the metal surface will be very low, and the metal surface will be debonded before the bonding strength of the carbon fiber peeling occurs; if the roughness is too large, the bonding strength of the metal interface may also be reduced.

[0013] Preferably, the roughness of the polished metal surface is 0.45 μm-0.5 μm (for example, 0.45 μm, 0.46 μm, 0.47 μm, 0.48 μm, 0.49 μm or 0.5 μm), and the roughness of the bonding area of ​​the milling surface of the carbon fiber composite material is 0.78 μm-0.83 μm (for example, 0.78 μm, 0.79 μm, 0.8 μm, 0.81 μm, 0.82 μm or 0.83 μm).

[0014] Preferably, the pre-coating liquid is prepared by a method comprising the following steps: mixing the nanoparticles, the first epoxy resin and the solvent to obtain a mixed liquid; subjecting the mixed liquid to a first ultrasound, followed by stirring with a stirrer, subjecting the mixed liquid to a second ultrasound after the stirring is completed, and obtaining the pre-coating liquid after the second ultrasound. The first ultrasound, stirring and the second ultrasound can achieve uniform mixing of the raw materials, and the nanoparticles do not settle. Specifically, the first ultrasound is to achieve a preliminary mixing of the first epoxy resin and the nanoparticles, and the nanoparticles will settle after magnetic stirring (the first epoxy resin is mixed evenly at this time), so ultrasound is performed again to evenly disperse the nanoparticles and minimize aggregation.

[0015] Preferably, the first ultrasonic time is 10-15min (e.g., 10min, 11min, 12min, 13min, 14min or 15min); the stirring speed is 800-1200r / min (e.g., 800r / min, 900r / min, 1000r / min, 1100r / min or 1200r / min), the stirring time is 1.5-2.5h (e.g., 1.5h, 1.8h, 2.0h, 2.3h or 2.5h); the second ultrasonic time is 20-30min (e.g., 20min, 22min, 25min, 28min or 30min). The parameters of the first ultrasonic, stirring and second ultrasonic can achieve uniform dispersion of each raw material.

[0016] Preferably, after the pretreatment is completed, the adhesive is applied to the bonding area and / or the surface of the metal to be bonded, and then the carbon fiber composite material and the metal to be bonded are placed in a fixing fixture, fixed and pressed, and the bonding of the milled surface of the carbon fiber composite material and the metal can be achieved after curing. The fixing fixture can achieve the appropriate relative position of the carbon fiber composite material and the metal to be bonded, and achieve the fixing and pressing of the two, thereby ensuring the bonding of the two.

[0017] Preferably, the adhesive comprises components of a second epoxy resin and a curing agent; the adhesive is obtained by first mixing and stirring the second epoxy resin and the curing agent, and then performing a degassing treatment.

[0018] Preferably, the first epoxy resin can be self-curing; alternatively, the first epoxy resin can be cured in combination with a curing agent in the adhesive.

[0019] Preferably, in the adhesive, the mass ratio of the second epoxy resin to the curing agent is 100:(44-49) (e.g., 100:44, 100:45, 100:46, 100:47, 100:48 or 100:49); the curing is performed at room temperature, and the curing time is 3-5 days (e.g., 3 days, 3.5 days, 4 days, 4.5 days or 5 days). If the curing time is too short, incomplete curing will result, and the optimal bonding strength will not be achieved.

[0020] Preferably, the adhesive is prepared by a method comprising the following steps: mixing the epoxy resin and the curing agent in proportion, stirring with a glass rod for 5-10 minutes (for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes), and after a large number of bubbles are generated, stirring with a magnetic stirrer at 350-500r / min (for example, 350r / min, 400r / min, 4500r / min or 500r / min) for 5-8 minutes (for example, 5 minutes, 6 minutes, 7 minutes or 8 minutes), and then placing in a vacuum centrifuge and centrifuging at a pressure of 0.1MPa and a speed of 1600r / min for 5-10 minutes (for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes) to remove the bubbles generated during the stirring process.

[0021] The method of the present invention has the following advantages:

[0022] The present invention uses a pre-coating liquid containing nanoparticles and epoxy resin to pre-treat the surface of the milled carbon fiber composite material, which can effectively improve the fiber peeling strength of the milled surface of the carbon fiber composite material, thereby improving its bonding strength with the metal. The method of the present invention overcomes the negative impact of the carbon fiber composite material on the bonding strength after machining, and has a wide range of application prospects.

[0023] The method of the invention can increase the average bonding strength between the treated carbon fiber composite material and the metal by 75.25%. The method of the invention is simple to operate and low in cost, and provides a new method and idea for improving the bonding reliability of machined carbon fiber composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic diagram of a single lap joint.

[0025] Figure 2 Curing tooling for single lap joints.

[0026] Figure 3 This is the tensile test diagram of a single lap joint.

[0027] Figure 4 This is the tensile shear result diagram of a single lap joint. DETAILED DESCRIPTION

[0028] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art should understand that the embodiments described below are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.

[0030] The main raw materials used in the following examples are:

[0031] The physical and mechanical properties of carbon fiber composite materials (T300, 3K twill weave, unidirectional ply [0]) are shown in Table 1 below:

[0032] Table 1 Physical and mechanical properties of carbon fiber composites

[0033]

[0034] The mechanical properties of titanium alloy (Ti-6Al-4V titanium alloy (GB / T3621-2007)) are shown in Table 2 below:

[0035] Table 2 Mechanical properties of titanium alloy

[0036]

[0037] In addition, the dimensions of the carbon fiber composite material (CFRP) and titanium alloy (Ti-6Al-4V) are 72 mm × 25 mm × 5 mm, and the length and width of the bonding area are 25 mm and 12 mm, respectively;

[0038] Adhesive used EA E-30CL TM Two-component epoxy adhesive;

[0039] The multi-walled carbon nanotubes were 95% pure multi-walled carbon nanotubes with a diameter of 10-15 nm and a length of 15-30 μm; the multi-walled carbon nanotubes were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. (China);

[0040] Al2O3 nanoparticles were purchased from Hebei Jincai Shengte Metal Materials Co., Ltd.;

[0041] SiC nanoparticles were purchased from Hebei Muyu New Materials Co., Ltd.

[0042] Example 1

[0043] The method of improving the bonding strength between the milled surface of the carbon fiber composite material and the metal in this embodiment comprises the following steps:

[0044] (1) Preparing a pre-coating solution: Mix multi-walled carbon nanotubes, a first epoxy resin ( EA E-30CL TMTwo-component epoxy adhesive) and acetone were poured into a beaker in a ratio of 1:40:360 and mixed. The mixture was first ultrasonically mixed for 10 minutes, then stirred on a magnetic stirrer at 1000 r / min for 2 hours to ensure sufficient mixing, and then placed in an ultrasonic bath for 30 minutes to fully disperse the multi-walled carbon nanotubes therein to avoid polymerization.

[0045] (2) The titanium alloy surface was polished with P22SiC sandpaper, where the roughness of the titanium alloy bonding surface was 0.47 μm, and the roughness of the bonding area of ​​the carbon fiber composite milling surface was 0.81 μm. The titanium alloy and the carbon fiber composite were then ultrasonically cleaned in acetone for 10 minutes to remove impurities such as oil, broken fibers, and sandpaper grains on the bonding surface.

[0046] (3) Pretreatment: Vertically immerse the bonding area of ​​the milled surface of the carbon fiber composite material that needs pretreatment in the pre-coating liquid, hold for 13 seconds, then quickly remove it and let it stand on a clean table for 1 minute. Finally, use non-linting memory foam to gently wipe the pre-coated surface to ensure that only a very small amount of resin remains. The average resin residue on the bonding area of ​​25 mm × 12 mm is 0.0017 g-0.0020 g.

[0047] (4) Adhesive preparation: Mix the second epoxy resin ( EA E-30CL TM Two-component epoxy adhesive) and curing agent were mixed in a ratio of 100:46, stirred with a glass rod for 5 minutes, and stirred with a magnetic stirrer at 350 r / min for 5 minutes after a large number of bubbles were generated. The mixture was then placed in a vacuum centrifuge and centrifuged at 0.1 MPa pressure and 1600 r / min for 10 minutes to remove the bubbles generated during the stirring process.

[0048] (5) Curing: The degassing adhesive is evenly applied to the surface of the material to be bonded (wherein the length and width of the bonding area of ​​the carbon fiber composite material are 25 mm and 12 mm, respectively; specifically, the adhesive can be applied to the metal surface, the bonding area of ​​the carbon fiber composite material, or the adhesive can be applied to the metal surface and the milling surface of the metal and carbon fiber composite material to be bonded at the same time), and the carbon fiber composite material (CFRP), titanium alloy sheet (Ti-6Al-4V), and standard gasket (thickness of 0.1 mm; the standard gasket is placed on the platforms on both sides of the groove of the corresponding bonding area of ​​the titanium alloy; the standard gasket can play a role in controlling the thickness of the adhesive) are placed in a fixed fixture and fixed and pressed (such as Figure 1-2 The prepared single lap joint and adhesive strip are placed at room temperature for curing for 3 days.

[0049] Example 2

[0050] The method of improving the bonding strength between the milled surface of the carbon fiber composite material and the metal in this embodiment comprises the following steps:

[0051] (1) Preparing a pre-coating solution: Al2O3 nanoparticles, a first epoxy resin ( EA E-30CL TM Two-component epoxy adhesive) and acetone were poured into a beaker in a ratio of 1:40:360 and mixed. The mixture was first ultrasonically mixed for 10 minutes, then stirred on a magnetic stirrer at 1000 r / min for 2 hours to ensure sufficient mixing, and then placed in an ultrasonic bath for 30 minutes to fully disperse the carbon nanotubes therein to avoid polymerization.

[0052] (2) The titanium alloy surface was polished with P22SiC sandpaper, where the roughness of the titanium alloy bonding surface was 0.47 μm, and the roughness of the bonding area of ​​the carbon fiber composite milling surface was 0.81 μm. The titanium alloy and the carbon fiber composite were then ultrasonically cleaned in acetone for 10 minutes to remove impurities such as oil, broken fibers, and sandpaper grains on the bonding surface.

[0053] (3) Pretreatment: Vertically immerse the bonding area of ​​the milled surface of the carbon fiber composite material that needs pretreatment in the pre-coating liquid, hold for 13 seconds, then quickly remove it and let it stand on a clean table for 1 minute. Finally, use non-linting memory foam to gently wipe the pre-coated surface to ensure that only a very small amount of resin remains. The average resin residue on the bonding area of ​​25 mm × 12 mm is 0.0017 g-0.0020 g.

[0054] (4) Adhesive preparation: Add the second epoxy resin ( EA E-30CL TM Two-component epoxy adhesive) and curing agent were mixed in a ratio of 100:46, stirred with a glass rod for 5 minutes, and stirred with a magnetic stirrer at 350 r / min for 5 minutes after a large number of bubbles were generated. The mixture was then placed in a vacuum centrifuge and centrifuged at 0.1 MPa pressure and 1600 r / min for 10 minutes to remove the bubbles generated during the stirring process.

[0055] (5) Curing: The degassing adhesive is evenly coated on the surface of the material to be bonded (wherein the length and width of the bonding area of ​​the carbon fiber composite material are 25 mm and 12 mm, respectively), and the carbon fiber composite material (CFRP), titanium alloy sheet (Ti-6Al-4V), and standard gasket (thickness of 0.1 mm; the standard gasket is placed on the platforms on both sides of the groove of the corresponding bonding area of ​​the titanium alloy; the standard gasket can play a role in controlling the thickness of the adhesive) are placed in a fixed fixture and fixed and pressed (such as Figure 1-2 The prepared single lap joint and adhesive strip are placed at room temperature for curing for 3 days.

[0056] Example 3

[0057] The method of improving the bonding strength between the milled surface of the carbon fiber composite material and the metal in this embodiment comprises the following steps:

[0058] (1) Preparing a pre-coating solution: SiC nanoparticles, a first epoxy resin ( EA E-30CL TM Two-component epoxy adhesive) and acetone were poured into a beaker in a ratio of 1:40:360 and mixed. The mixture was first ultrasonically mixed for 10 minutes, then stirred on a magnetic stirrer at 1000 r / min for 2 hours to ensure sufficient mixing, and then placed in an ultrasonic bath for 30 minutes to fully disperse the carbon nanotubes therein to avoid polymerization.

[0059] (2) The titanium alloy surface was polished with P22SiC sandpaper, where the roughness of the titanium alloy bonding surface was 0.47 μm, and the roughness of the bonding area of ​​the carbon fiber composite milling surface was 0.81 μm. The titanium alloy and the carbon fiber composite were then ultrasonically cleaned in acetone for 10 minutes to remove impurities such as oil, broken fibers, and sandpaper grains on the bonding surface.

[0060] (3) Pretreatment: Vertically immerse the bonding area of ​​the milled surface of the carbon fiber composite material that needs pretreatment in the pre-coating liquid, hold for 13 seconds, then quickly remove it and let it stand on a clean table for 1 minute. Finally, use non-linting memory foam to gently wipe the pre-coated surface to ensure that only a very small amount of resin remains. The average resin residue on the bonding area of ​​25 mm × 12 mm is 0.0017 g-0.0020 g.

[0061] (4) Adhesive preparation: Add the second epoxy resin ( EA E-30CL TM Two-component epoxy adhesive) and curing agent were mixed in a ratio of 100:46, stirred with a glass rod for 5 minutes, and stirred with a magnetic stirrer at 350 r / min for 5 minutes after a large number of bubbles were generated. The mixture was then placed in a vacuum centrifuge and centrifuged at 0.1 MPa pressure and 1600 r / min for 10 minutes to remove the bubbles generated during the stirring process.

[0062] (5) Curing: The degassing adhesive is evenly coated on the surface of the material to be bonded (wherein the length and width of the bonding area of ​​the carbon fiber composite material are 25 mm and 12 mm, respectively), and the carbon fiber composite material (CFRP), titanium alloy sheet (Ti-6Al-4V), and standard gasket (thickness of 0.1 mm; the standard gasket is placed on the platforms on both sides of the groove of the corresponding bonding area of ​​the titanium alloy; the standard gasket can play a role in controlling the thickness of the adhesive) are placed in a fixed fixture and fixed and pressed (such as Figure 1-2The prepared single lap joint and adhesive strip are placed at room temperature for curing for 3 days.

[0063] Comparative Example 1

[0064] The difference between this comparative example and Example 1 is that the carbon nanotubes in the pre-coating liquid are omitted; the rest are consistent with Example 1.

[0065] Comparative Example 2

[0066] The difference between this comparative example and Example 1 is that the step of pretreating the bonding area of ​​the milling surface of the carbon fiber composite material with the pre-coating liquid is omitted; the rest is consistent with Example 1.

[0067] Comparative Example 3

[0068] The difference between this comparative example and Example 1 is that: after standing for 1 minute in step (3), steps (4) and (5) are directly carried out (i.e., the step of wiping with non-depilatory memory cotton in step (3) is omitted; the residual amount of the first epoxy resin in this comparative example is 0.007-0.008 g / mm 2 ); the rest are consistent with Example 1.

[0069] Experimental example

[0070] Tensile shear test: Fix the cured single lap joint on a tensile machine (such as Figure 3 As shown), tensile shear tests were carried out; wherein, the tensile rate of the single lap joint was 1 mm / min, and each experiment was repeated at least three times.

[0071] The tensile shear results of a single lap joint are as follows Figure 4 As shown in Table 3 below.

[0072] Table 3 Shear strength test results

[0073]

[0074]

[0075] Note: The improvement ratio in Table 3 is calculated based on Comparative Example 2.

[0076] from Figure 4As can be seen from Table 3, after pretreatment with a precoating liquid without adding multi-walled carbon nanotubes (Comparative Example 1), the average bonding shear strength between the milling surface of the carbon fiber composite material and the titanium alloy is slightly improved, only 15.47%; pretreatment of the milling surface of the carbon fiber composite material with a precoating liquid added with Al2O3 nanoparticles and SiC nanoparticles helps to improve the average bonding shear strength between the milling surface of the carbon fiber composite material and the titanium alloy, which is better than Comparative Example 1. After adding multi-walled carbon nanotubes with a mass fraction of 0.25% to the precoating liquid (Example 1), the average bonding strength reaches 20.28MPa, which is 75.3% higher than that without treatment (Comparative Example 2), which can significantly improve the average bonding shear strength between the milling surface of the carbon fiber composite material and the titanium alloy.

[0077] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A method for improving the bonding strength between a milled surface of a carbon fiber composite material and a metal, characterized in that: The carbon fiber composite material milling surface has a bonding area, and the bonding area is used to bond with metal; the bonding strength between the carbon fiber composite material milling surface and the metal is improved by pre-treating the bonding area; The pretreatment comprises the following steps: treating the bonding area with a pre-coating liquid; the pre-coating liquid comprises nanoparticles, a first epoxy resin and a solvent.

2. The method according to claim 1, characterized in that The pretreatment can be achieved by soaking the bonding area in a pre-coating liquid, taking it out of the pre-coating liquid and letting it stand, and then reducing the residual amount of the first epoxy resin in the bonding area.

3. The method according to claim 2, characterized in that The bonding area is soaked in the pre-coating liquid for 10-15 seconds; After being taken out, the film was allowed to stand for 1 minute, and the residual amount of the first epoxy resin in the bonding area was reduced to 0.0017-0.0020 g / 300 mm 2 .

4. The method according to claim 1, characterized in that In the pre-coating liquid, the mass ratio of the nanoparticles, the epoxy resin and the solvent is 1:(38-42):

360.

5. The method according to claim 1, characterized in that Before the pretreatment, the method further includes a step of grinding the bonding area and the metal surface.

6. The method according to claim 1, characterized in that The pre-coating liquid is prepared by a method comprising the following steps: mixing the nanoparticles, epoxy resin and solvent to obtain a mixed liquid; The mixed liquid is subjected to a first ultrasonic treatment, and then stirred by a stirrer. After the stirring is completed, the mixed liquid is subjected to a second ultrasonic treatment, and the pre-coating liquid is obtained after the second ultrasonic treatment is completed.

7. The method for improving the bonding strength between the milled surface of carbon fiber composite material and metal according to claim 6, characterized in that: The first ultrasound duration is 10-15 minutes; The stirring speed is 800-1200 r / min, and the stirring time is 1.5-2.5 h; The second ultrasound duration is 20-30 min.

8. The method according to any one of claims 1 to 7, characterized in that After the pretreatment is completed, the adhesive is applied to the bonding area and / or the surface of the metal to be bonded, and then the carbon fiber composite material and the metal to be bonded are placed in a fixed tooling, fixed and pressed, and after curing, the bonding of the milled surface of the carbon fiber composite material and the metal can be achieved.

9. The method according to claim 8, characterized in that The components of the adhesive include a second epoxy resin and a curing agent; The adhesive is obtained by mixing and stirring the epoxy resin and the curing agent, and then performing a degassing treatment.

10. The method according to claim 8, characterized in that In the adhesive, the mass ratio of the epoxy resin to the curing agent is 100:(44-49); The curing is carried out at room temperature and the curing time is 3-5 days.